1991
DOI: 10.1038/bjc.1991.141
|View full text |Cite
|
Sign up to set email alerts
|

pNR-2/pS2 immunohistochemical staining in breast cancer: correlation with prognostic factors and endocrine response

Abstract: Summary Expression of the oestrogen-regulated pNR-2/pS2 protein has been studied in paraffin sections

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
58
1
2

Year Published

1994
1994
1997
1997

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(72 citation statements)
references
References 32 publications
11
58
1
2
Order By: Relevance
“…pS2, a small cysteine-rich protein of unknown function, appeared with ER to be strongly correlated with tamoxifen-induced tumour regression. This had already been suggested by others (Henry et al, 1989(Henry et al, , 1991Schwartz et al, 1991;Hurlimann et al, 1993;Wilson et al, 1994). We were unable to show a link between response to tamoxifen and c-erbB-2 or GSTi expression, contrary to previous studies (Wright et al, 1992;Nicholson et al, 1993;Dorion-Bonnet et al, 1993).…”
supporting
confidence: 64%
“…pS2, a small cysteine-rich protein of unknown function, appeared with ER to be strongly correlated with tamoxifen-induced tumour regression. This had already been suggested by others (Henry et al, 1989(Henry et al, , 1991Schwartz et al, 1991;Hurlimann et al, 1993;Wilson et al, 1994). We were unable to show a link between response to tamoxifen and c-erbB-2 or GSTi expression, contrary to previous studies (Wright et al, 1992;Nicholson et al, 1993;Dorion-Bonnet et al, 1993).…”
supporting
confidence: 64%
“…In pilot studies involving 21 patients with recurrent disease, PS2 at the transcriptional level was predictive for endocrine responsiveness (Henry et al, 1989;Skilton et al, 1989). Similar results were obtained with immunohistochemically assessed PS2 status in small series of 35 (Henry et al, 1991) and 72 patients (Schwartz et al, 1991), but these findings were not confirmed by Luqmani et al (1993a) in a study involving 70 patients.…”
supporting
confidence: 62%
“…Similar results with respect to a relationship between PS2 expression and (relapse-free) survival were obtained when PS2 transcripts were analysed (Thompson et al, 1993). On the other hand, immunohistochemically assessed PS2 status was of no or only marginal prognostic value (Henry et al, 1991;Cappelletti et al, 1992;Thor et al, 1992). In pilot studies involving 21 patients with recurrent disease, PS2 at the transcriptional level was predictive for endocrine responsiveness (Henry et al, 1989;Skilton et al, 1989).…”
supporting
confidence: 62%
See 2 more Smart Citations